Physical properties and food safety of edible bioplastic films prepared from nata de tomato blend - Adristi, Fionna Fabiola; Suniati, Fransisca Romana Titis; Sulistyo, Joko (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Edible film is a thin layer that can be digested by the body and used as food packaging. The manufacture of edible films utilizes bacterial cellulose fibers from nata de tomato as a reinforcing material. This study evaluates the physical characteristics, structure, and food safety of edible films made from nata de tomato. The tested sample contains 2.5% nata de tomato with 1% glycerin and other additives. Physical analysis includes thickness, tensile strength, elongation, density, opacity, moisture content, and water solubility. The structure was examined using FTIR and SEM, while food safety testing involved heavy metal analysis (As, Cd, Pb, Hg) and microbiological testing (Escherichia coli, Salmonella spp., and Staphylococcus aureus). The results show that physical characteristics such as thickness, tensile strength, density, opacity, moisture content, and water solubility meet feasibility standards, although the low elongation requires the addition of glycerin. FTIR and SEM analyses indicate that cellulose polymers are the main component of the edible film. The edibility test shows that the edible films made from nata de tomato are safe from heavy metal and microbial contamination.